Using strong lensing to understand the microJy radio emission in two radio quiet quasars at redshift 1.7. Issue 3 (18th October 2021) - Hartley, P; Jackson, N; Badole, S; McKean, J P; Sluse, D; Vives-Arias, H
ABSTRACT: The radio quasar luminosity function exhibits an upturn around L_6\:GHz=10^23 W Hz −1 that is well-modelled by a star-forming host galaxy population. This distribution leads some authors to cite star formation as the main radio emission mechanism in so-called radio-quiet quasars (RQQs). Understanding the origin of RQQ radio emission is crucial for our understanding of quasar feedback mechanisms – responsible for the regulation of star formation in the host galaxy – and for understanding galaxy evolution as a whole. By observing RQQs that have been magnified by strong gravitational lensing, we have direct access to the RQQ population out to cosmic noon, where evidence for twin mini-jets has recently been found in a sub-μ Jy RQQ. Here we present radio observations of two lensed RQQs using the VLA at 5 GHz, the latest objects to be observed in a sample of quadruply-imaged RQQs above −30°. In SDSS J1004+4112 we find strong evidence for AGN-related radio emission in the variability of the source. In PG 1115+080 we find tentative evidence for AGN-related emission, determined by comparing the radio luminosity with modelled dust components. If confirmed in the case of PG 1115+080, which lies on the radio–FIR correlation, the result would reinforce the need for caution when applying the correlation to rule out jet activity and when assuming no AGN heating of FIR-emitting dust when calculating star formation rates. Our programme so far has shown that the two of the faintest radio sources ever imaged show strong evidence for AGN-dominated radio emission.